Pelatihan Tim Pendamping Keluarga (TPK) Dalam Mendampingi Calon Pengantin sebagai Upaya Pencegahan Stunting di Kabupaten Blora - Yuwanti; Anita Lufianti; Fitriani; Nurulistyawan TP (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2022)
Background: Stunting is a nutritional problem in the First 1000 Days of Life. Efforts to prevent stunting starting from preconception to 2 years of birth require participation from various parties and various efforts from fulfilling nutrition to changing behavior.   Purpose: Provide training for the Family Assistance Team (TPK) in assisting brides-to-be as an effort to prevent stunting.   Method: The method used in this community service is a training for TPK members. The training participants were 90 people from 10 villages in Blora Regency.   Results: The results of community service obtained the knowledge of the Family Assistance Team has increased, namely good knowledge of 96.7%.   Conclusion: Training for the Family Assistance Team (TPK) is effective in increasing TPK's knowledge about stunting in accompanying brides-to-be as an effort to reduce stunting.